Determinants of Maternity Leave Duration in Australia: Evidence from the HILDA Survey - Ulker, A; Guven, C (My University, 2011)
We use the first five waves of the Household, Income and Labour Dynamics in Australia survey to examine what determines the maternity leave taken by pre-birth employed mothers of newborn children in Australia. We find that the difficulties faced by mothers in finding appropriate child care in terms of both cost and quality hinder them from returning to the labour market following childbirth. Maternity leave entitlements lead to an earlier return to the labour market following the birth of a child, relative to those who have no leave rights at all. Mothers with higher wages in their pre-birth employment and mothers with higher education levels tend to return to the labour market earlier than their lower wage and less educated counterparts. More flexible pre-birth jobs are associated with an increase in the likelihood of mothers returning to the workforce earlier than the average. Household wealth, however, seems to play a facilitating role in mothers taking a longer period of maternity leave to look after the newborn child. That is, mothers who have higher wealth levels can ‘afford’ to stay on maternity leave longer, to look after their children better during their primary developmental months. We believe that this article provides useful insights into the employment transitions of Australian mothers after having a baby.
Economic Record
Keywords: Employment -- Parental leave; Labour market; Employment; Parental leave; Employment and unemployment